2021
DOI: 10.1080/15504263.2021.1962205
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Increases Sensorimotor Gating and is Related to Psychopathy

Abstract: Objective: Prepulse inhibition regulates sensorimotor gating and is a marker of vulnerability to certain disorders. We compared prepulse inhibition, psychopathy, and sensitivity to punishment and reward in patients with cocaine-related disorder without psychiatric comorbidities and a control group. Methods: This was an observational study of a sample of 22 male cases with cocaine-related disorder and 22 healthy male controls. We used the Psychiatric Research Interview for Substance and Mental Disorders and Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…With regard to the results from studies with substance use disorders patients, almost none of the studies found differences between patients and controls in the startle response (72.2%), except for one study that found a lower magnitude among patients using cocaine [ 134 ], and two studies that did not report data on this measure [ 142 , 144 ]. Regarding PPI in patients using cannabis, all reviewed studies observed lower prepulse inhibition than subjects in the control group [ 137 139 , 141 , 142 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the results from studies with substance use disorders patients, almost none of the studies found differences between patients and controls in the startle response (72.2%), except for one study that found a lower magnitude among patients using cocaine [ 134 ], and two studies that did not report data on this measure [ 142 , 144 ]. Regarding PPI in patients using cannabis, all reviewed studies observed lower prepulse inhibition than subjects in the control group [ 137 139 , 141 , 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding PPI in patients using cannabis, all reviewed studies observed lower prepulse inhibition than subjects in the control group [ 137 139 , 141 , 142 ]. Conversely, in studies evaluating patients using cocaine, a generally higher PPI was found among patients compared to controls [ 134 , 140 , 143 , 144 ]. Similarly, one of the reviewed studies analyzing ecstasy found the same trend [ 135 ] while another did not find any differences [ 136 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, sociodemographic data about the participants were also collected using the Addictive Disorders Network tool [ 42 ].…”
Section: Methodsmentioning
confidence: 99%